Revealing a High Water Abundance in the Upper Mesosphere of Mars With ACS Onboard TGO. Issue 10 (25th May 2021) - Belyaev, Denis A.; Fedorova, Anna A.; Trokhimovskiy, Alexander; Alday, Juan; Montmessin, Franck; Korablev, Oleg I.; Lefèvre, Franck; Patrakeev, Andrey S.; Olsen, Kevin S.; Shakun, Alexey V.
Abstract: We present the first water vapor profiles encompassing the upper mesosphere of Mars, 100–120 km, far exceeding the maximum altitudes where remote sensing has been able to observe water to date. Our results are based on solar occultation measurements by Atmospheric Chemistry Suite (ACS) onboard the ExoMars Trace Gas Orbiter (TGO). The observed wavelength range around 2.7 μm possesses strong CO2 and H2 O absorption lines allowing sensitive temperature and density retrievals. We report a maximum H2 O mixing ratio varying from 10 to 50 ppmv at 100–120 km during the global dust storm (GDS) of Martian Year (MY) 34 and around southern summer solstice of MY 34 and 35. During other seasons water remains persistently below ∼2 ppmv. We claim that contributions of the MY34 GDS and perihelion periods into the projected hydrogen escape from Mars are nearly equivalent. Plain Language Summary: We report regular events of high abundances of the water vapor (H2 O) in the upper atmosphere of Mars (100–120 km). So far, any water enrichment has not been revealed by remote sensing at such high altitudes. Higher than 80 km, solar light breaks water vapor molecules into H and O atoms, which may reach the exosphere and escape the planet. When Mars is closer to the Sun (the perihelion season), the atmosphere's circulation intensifies, causing increased dust activity with global dust storms (GDS), occurring every 3–4 Mars years. We observed during the second halves of Martian years 34 and 35 (2018–2020), including one GDS and two perihelion seasons. We report that the maximum water relative abundance reaches 10–50 parts per million in volume (ppmv) at 100–120 km during the GDS and every perihelion season. These high values indicate that the Martian atmosphere above 100 km regularly hosts large amounts of water, facilitating the long‐term escape of water from the planet. Key Points: Water abundances are reported in a previously unexplored altitude range: from 100 to 120 km The observed GDS (MY34) and two perihelion seasons (MY34, 35) reveal the H2O content around 10–50 parts per million by volume at 100–120 km Contributions of the MY34 GDS and perihelion periods into the projected hydrogen escape from Mars are nearly equivalent